The Influence of Job Satisfaction, Work Life Balance and Career Growth on Hospitality Professionals’ Transition to Allied Sectors ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2025)
Background: The hospitality industry has traditionally offered dynamic career opportunities within core hotel operations. However, over the past decade, there has been a notable shift of hospitality professionals from core hotel roles to allied sectors such as event management, tourism and consulting. This career movement has raised concerns regarding the sustainability of talent retention within hotel operations. Understanding the key factors influencing this shift is essential for developing effective strategies to improve employee satisfaction and retention in the industry. Objective: The study aimed to examine the impact of job satisfaction, work-life balance and career growth opportunities on the career transitions of hospitality professionals from core hotel operations to allied sectors. It sought to identify the underlying motivations for these movements and explore potential measures that could help hotel management retain skilled professionals. Methodology: A quantitative research design was adopted. The study was conducted in urban hospitality hubs where career transitions are more prevalent. A total of 130 hospitality professionals who had moved from core hotel operations to allied sectors participated in a structured survey. The survey utilized a structured questionnaire focusing on job satisfaction, work-life balance, career growth opportunities and professional motivations. Data analysis was performed using descriptive and inferential statistics. Results: The findings indicated that job dissatisfaction, poor work-life balance and limited career growth opportunities were significant drivers of career shifts among hospitality professionals. A majority of respondents reported seeking roles in allied sectors due to better work-life balance, structured work environments and enhanced career mobility. The study also found that professionals were attracted to allied industries offering more defined career progression pathways and greater job stability. Additionally, qualitative insights highlighted the role of workplace culture, managerial support and personal aspirations in influencing career decisions. Conclusion: The study concluded that the hospitality industry must prioritize job satisfaction, work-life balance and career development opportunities to retain skilled professionals. Enhancing career growth prospects, implementing employee-friendly work schedules and fostering supportive work environments could mitigate the trend of professionals shifting to allied sectors. These insights provide valuable recommendations for hotel management and policymakers in developing effective retention strategies to sustain a competent and motivated workforce in core hotel operations.
Keywords: Hospitality professionals; job satisfaction; work-life balance; career growth; core hotel operations; allied sectors; career transitions; talent retention; hospitality workforce; professional motivations